The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1021/ma0359335
|View full text |Cite
|
Sign up to set email alerts
|

Free Volume and Density Gradients of Amorphous Polymer Surfaces As Determined by Use of a Pulsed Low-Energy Positron Lifetime Beam and PVT Data

Abstract: Density gradient widths at the polymer−vacuum surfaces of poly(methyl methacrylate), styrene-co-acrylonitrile, and styrene-co-maleic anhydride were quantified to 2, 5, and 4 nm, respectively, by use of a pulsed low-energy positron lifetime beam and to approximately 1.5 nm for all three polymers on the basis of theoretical predictions from pressure−volume−temperature (PVT) data, making use of the Cahn−Hilliard theory of inhomogeneous systems in conjunction with the Sanchez−Lacombe lattice fluid theory. Excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 77 publications
2
30
0
Order By: Relevance
“…For example, structural defects and chemical modifications generated by irradiation modification of materials with highly energetic ions (170)(171)(172) or chemical (173)(174)(175) treatments can be investigated. Other fields include the study of interfaces between bilayers (176)(177)(178)(179) and the glass transition as a function of thickness of very thin films (180).…”
Section: Application To Polymers Monoenergetic Positron Beams Can Bementioning
confidence: 99%
“…For example, structural defects and chemical modifications generated by irradiation modification of materials with highly energetic ions (170)(171)(172) or chemical (173)(174)(175) treatments can be investigated. Other fields include the study of interfaces between bilayers (176)(177)(178)(179) and the glass transition as a function of thickness of very thin films (180).…”
Section: Application To Polymers Monoenergetic Positron Beams Can Bementioning
confidence: 99%
“…The WLF equation acquires physical significance when examined in the light of the theory of free volume [28]. The constants then become:…”
Section: Quantitative Treatment Of Experimental Data To Facilitate Inmentioning
confidence: 99%
“…Glass transition in the sub-surface regions of polymers was studied by several groups [25][26][27][28][39][40][41]. Glass transition appears as an inflection in the temperature dependence of the free volume size, so for the mere determination of the glass transition temperature (T g ) DBAR can be used as well as PALS (see Fig.…”
Section: Studies Of Free Volume and Poresmentioning
confidence: 99%
“…However, Algers et al reported that the enhancement is observable only at depths shallower than a few nm for polystyrene, PMMA, SAN and poly(styrene-co-maleic anhydride) (SMA) [39]. The discrepancy may partly arise from the different method to account for the very long lifetimes due to o-Ps annihilating in vacuum [25].…”
Section: Studies Of Free Volume and Poresmentioning
confidence: 99%